Effect of a Sleep Hygiene Education Program Using Telephone Follow-up Method on the Sleep Quality of the Elderly - Maryam Moradi; Hamideh Mohammadzadeh; Reza Noori; Kokab Basiri Moghadam; Leila Sadeghmoghadam (University of Social Welfare & Rehabilitation Sciences, 2021)
Objectives: Low quality sleep is one of the most common problems in old age. The present study aims to determine the effect of a sleep hygiene education program using Telephone Follow-Up (TFU) method on the sleep quality of the elderly. Methods & Materials: This quasi-experimental study was conducted on 80 eligible elderly people aged 60-74 years who were selected using a systematic random sampling method and were randomly assigned into intervention and control groups. The intervention group received a one-hour face-to-face education session on sleep hygiene. The TFU were carried out two times per week in the first month and once a week in the second month after intervention. The control group received routine care. The data collection tools were a demographic form and the Pittsburgh Sleep Quality Index (PSQI) questionnaire. The PSQI was completed for both groups immediately after the second month. Results: There was no statistically significant difference in the mean PSQI score before intervention in the intervention (8.02) and control (7.47) groups (P=0.32), but after the intervention, the mean PSQI score in the intervention group (5.42) was significantly reduced compared to the control group (7.67) (P<0.001). Conclusion: Sleep hygiene education program based on TFU improves the sleep quality of the elderly. It is recommended that health care providers use this method to improve the sleep quality of the elderly.